A Random Sampling from the World of Modern Poetry (KULT_online, 2009)
This collection of articles from the field of literary studies attempts to trace forms and patterns in new contemporary poetry through a selection of detailed analyses. The focus lies on the interaction of interior and exterior, of perception and formulation, of varieties of creation and reception. The assembled contributions range from a description of metalyric self-reflexion to the (still evident) critique of civilization in a global context. They pinpoint traditional references on the one and apparent singular perspectives on the other hand. This diversity turns the anthology into a true collection – one that cannot provide an all-encompassing overview, but instead spotlights the most diverse aspects of 21st Century poetry.